25-hydroxyl Vitamin D Levels and the Risk of Mortality in the General Population - Melamed, Michal L. (2008)
BACKGROUND: In dialysis patients, activated vitamin D therapy is associated with reduced mortality. Observational data suggests that low 25-hydroxyl vitamin D levels are associated with diabetes mellitus, hypertension and cancers. However, whether low serum 25-hydroxyl vitamin D (25(OH)D) levels are associated with mortality in the general population is unknown. METHODS: We tested the association of low 25(OH)D levels with all-cause, cancer and cardiovascular disease (CVD) mortality in 13,331 nationally representative adults ≥20 years old from the Third National Health and Examination Survey (NHANES III) Linked Mortality Files. Participant vitamin D levels were collected in 1988-1994 and individuals were passively followed for mortality through 2000. RESULTS: In cross-sectional multivariable analyses, increasing age, female sex, non-white race/ethnicity, diabetes, current smoking, and higher BMI were all independently associated with higher odds of 25(OH)D deficiency (lowest quartile of 25(OH)D <17.8 ng/ml), while greater physical activity, vitamin D supplementation and non-winter season were inversely associated. During a median 8.7 years of follow-up, there were 1806 deaths including 777 from CVD. In multivariable models (adjusted for baseline demographics, season, traditional and novel CVD risk factors), compared to the highest quartile, 25(OH)D levels <17.8 ng/ml were associated with a 26% increased rate of all-cause mortality (1.26, 95% CI 1.08-1.46) and a population attributable risk of 3.1%. The adjusted models of CVD and cancer mortality revealed a higher risk which was not statistically significant. CONCLUSIONS: The lowest quartile of 25(OH)D (<17.8 ng/ml) is independently associated with all-cause mortality in the general population.